(In)stability at the Cowles Commission (1939–1948). Issue 4 (3rd July 2020) - Assous, Michaël; Carret, Vincent
Abstract: Stability analysis touched off extensive discussions at the Cowles Commission between 1939 and 1948. Oskar Lange, later followed by Lawrence Klein and Don Patinkin, among others, advocated for a move from a static analysis aimed at proving the existence of a stationary equilibrium with unemployment towards a dynamic approach exploring stability properties of full employment equilibria. In presence of excess supply of goods and labour with flexible money wages and prices, the message was that macroeconomic pathologies are better regarded as disequilibrium dynamics when full employment equilibrium is unstable – Lange and Klein – or when it is stable – Patinkin. The objective of this paper is to examine this type of modelling and how it provided the basis of a specific political vision shared by most economists of the Cowles Commission in the 1940's.